Enhancing strength while preserving elongation: A study on copper after accumulative skin pass rolling. (15th November 2021) - Wang, Rui; Lu, Cheng; Davis, Bradley; Zhang, Che; Li, Jiaqing; Tieu, Kiet A.; Gazder, Azdiar A.
Highlights: A modified rolling approach (accumulative skin pass rolling) was applied to fabricate gradient microstructure in copper sheets and has potential to fabricate large-volume gradient materials. Gradient microstructure results in a good combination of high yield strength (from ∼70 to 153 MPa) and uniform elongation (∼0.3). The contribution of dislocation strengthening to improvement of yield strength is more remarkable than grain boundary strengthening in the heterogeneous structure. Abstract: Current surface mechanical treatment techniques that produce gradient microstructures and return a combination of high strength and high uniform elongation are limited in terms of their industrial suitability. This study applies a modified surface rolling strategy, namely accumulative skin pass rolling (ASPR), to produce a gradient microstructure in copper and return an increase in yield strength while preserving high uniform elongation. Uniaxial tension combined with in-situ electron back-scattering diffraction compared the variations in mechanical properties and microstructure after annealing and ASPR. The increase in yield strength after ASPR is ascribed to the higher dislocation density at subgrain and grain boundaries, junctions and interiors whereas the preservation of uniform elongation is due to the gradient microstructure comprising a range of grain sizes across the sheet thickness. Finite element analysis of ASPR samples revealed strain heterogeneity along the gauge length and a transfer of load from softer grains in the sheet interior to harder grains closer to the sheet surface during tension. The results indicate that ASPR may be a promising new strategy for the continuous fabrication of sheets with gradient microstructures. Graphical abstract: Image, graphical abstract